2013
DOI: 10.5539/jmsr.v2n3p60
|View full text |Cite
|
Sign up to set email alerts
|

Study on Patch Bonding for Recovery of Damaged Carbon Fiber Reinforced Thermoplastics Subjected to Four-Point Bending Load

Abstract: The purpose of this study is to investigate the fracture behavior and repairability of carbon fiber reinforced thermoplastics (CFRTP). At first, four-point bending tests were conducted to characterize the bending characteristics of fabricated CFRTP. The test results show that local delamination first appeared when the applied bending strain was 2.0%. When the bending strain reached 2.5%, the failure of the fiber due to local buckling was observed at the compression side of the specimen. Secondly, the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…1,5 Among the CFRP, carbon-fiber-reinforced thermoplastics (CFRTP) are expected to have better mass productivity and recyclability than the conventionally used thermosetting CFRP. 4,6,7 Many studies on the improvement of mass productivity of CFRTP have been reported, 8 but their recyclability remains to be considered, although thermoplastic polymer can be re-melted and reshaped. As a method to mold CFRTP, carbon fiber thermoplastic prepreg sheets heated and pressed after having been cut into a desired shape and stacked.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Among the CFRP, carbon-fiber-reinforced thermoplastics (CFRTP) are expected to have better mass productivity and recyclability than the conventionally used thermosetting CFRP. 4,6,7 Many studies on the improvement of mass productivity of CFRTP have been reported, 8 but their recyclability remains to be considered, although thermoplastic polymer can be re-melted and reshaped. As a method to mold CFRTP, carbon fiber thermoplastic prepreg sheets heated and pressed after having been cut into a desired shape and stacked.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of long-fiber composites, owing to their anisotropic mechanical characteristics, interlaminar failure often occurs between the layers in the first or second stage of fracturing (Nishikawa, et al, 2006). Such failure is also seen in the case of CFRTPs (Obunai, et al, 2013), while CFRTPs have higher fracture toughness than Carbon-fiber-reinforced-thermosets (CFRTS). In the case of CFRTS, a number of methods for increasing the interlaminar toughness, such as the modification of the matrix (Kim, et al, 1992), stitching of reinforcements (Liu, 1991), and Z-pining (Dai, et al, 2004), have been proposed.…”
Section: Introductionmentioning
confidence: 99%